Food security and family farming - Gordillo de Anda, Gustavo (2004)
Discusses the viability of a type of programmatic proposal deriving from the Rome Declaration and Plan of Action signed by the Governments of 148 countries. Suggests that the implementation of the Plan of Action requires the establishment of a structural link between the population affected by the food insecurity and the various authorities responsible for initiating public action. Opines that htis structural link can be centred upon family farmers. Argues that food security, underpinned by the right to food, is a territorial expression of civic rights.